Import competition in the manufacturing sector in Peru: Its impact on informality and wages - Martha Denisse Pierola; Dennis Sanchez-Navarro (Inter-American Development Bank (IDB), 2019)
This paper studies the impact of import competition from China on informality and wages in the Peruvian manufacturing sector in 20012010. Using data from the Peruvian Household Survey, we use a two-step procedure to evaluate the impact of the surge in imports from China on the likelihood of being hired in the informal sector and on wages in both the formal and informal sectors. The results suggest that greater import competition increased the chances of working in the informal sector among workers with only elementary educationarguably one of the less-skilled groups. Regarding the impact on real wages, we find that the increase in imports from China was also detrimental to the least-educated workers (those with an elementary-level education or no education at all). The evidence is more mixed among better-educated workers in the formal sector: their wages improved, but the result is only significant once industry output growth is accounted for.
Keywords: F14; F16; J23; 330; import competition; informality; wages